Production of solketal from glycerol and acetone over an amberlyst-35 catalyst a plant design - Delos Santos, Troy; Marasigan, Gilbert C.; Morales, Emmanuel Ricardo G.; Dela Cruz, John Von Wernher C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The studies that explored the potential of solketal as a fuel additive had significantly increased in number due to the chemical's promising fuel enhancing properties and high initial economic value. However, because solketal is still a relatively new compound in the market, studies about its plant-wide production are still lacking. With these in mind, the technical and economic feasibility of a Limay Solketal Chemical Plant was studied in this paper. The process of producing solketal in this study considered a mixing and reaction step of the raw materials acetone and glycerol followed by a series of separation processes. Furthermore, this study did not only consider the production of solketal as a valuable product but it also provided an alternative pathway for the utilization of the significantly increasing glycerol produced as a byproduct from the fast-growing biodiesel industry. On the process side, the industrial production of solketal was technically feasible. With a design plant capacity of 296 M7day of Sockeldi, the design involved industry-standard equipment. The mixing tank was sized for a two-hour residence time, leading to an adiabatic fixed bed reactor designed to maximize solketal yield without complicated temperature controls. A series of distillation columns were designed to recycle excess reactants (acetone and glycerol), recover the solvent for recirculation, and purify the solketal product to 99.5 % to allow for some deviation to the 97 % product specification. The storage tanks were good for 7 days of residence time, to ensure any issues on the supply of raw materials or the delivery of solketal product were buffered. To ensure the accuracy of the design, the simulation software Aspen Plus® was used for the calculations. With the design as stated, a pessimistic economic analysis of the plant projected a payback of 8.12 years, an internal rate of return (IRR) of 21 %, and a net present value (NPV) of 19.5M USD. It was concluded that the proposed Limav Solketal Chemical Plant was both technically and economically feasible in the Philippines. Further exploration of the technical feasibility of a plant-wide production of solketal together with a more detailed economic analysis was recommended to help in further establishing the potential of solketal as a promising fuel additive.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Fuel -- Additives; Chemical plants -- Design and construction; Solketal